The Lady Has A Past: Burning Cove # 5 - Quick, Amanda; Hallett, Morgan ([Prince Frederick, Maryland] : Recorded Books, Inc., 2021)
Investigative apprentice Lyra Brazier, the newest resident of Burning Cove, is unsettled when her boss suddenly goes on a health retreat at an exclusive spa and disappears without another word. Lyra knows something has happened to Raina Kirk, and she is the only one who can track her down. The health spa is known for its luxurious offerings and prestigious clientele, and the wealthy, socialite background Lyra desperately wanted to leave behind is perfect for this undercover job. The agency brings in a partner and bodyguard for her, but she doesn't get the suave, pistol-packing private eye she expected. Simon Cage is a mild-mannered antiquarian book dealer with a quiet, academic air, and Lyra can't figure out why he was chosen as her partner. But it soon becomes clear when they arrive at the spa and pose as a couple: Simon has a unique gift that allows him to detect secrets, a skill that is crucial in finding Raina.
Title from web page.
Compact discs.
new cdbk 2022 summer.
Narrated by Morgan Hallett.
Keywords: Missing persons -- Investigation -- Fiction; Women private investigators -- Fiction; Antiquarian booksellers -- Fiction; Socialites -- Fiction; Undercover operations -- Fiction; Health resorts -- Fiction; Murder -- Fiction; Man-woman relationships -- Fiction; Antiquarian booksellers; Health resorts; Man-woman relationships; Missing persons -- Investigation; Murder; Socialites; Undercover operations; Women private investigators; California -- Fiction; California; Audiobooks; Detective and mystery fiction; Fiction; Sound recordings; Thriller fiction; Historical fiction; Romance fiction; Detective fiction; Mystery fiction